Knowledge, attitudes and practice of physicians towards fertility and pregnancy-related issues in youngBRCA-mutated breast cancer patients. Issue 5 (May 2019) - Lambertini, Matteo; Di Maio, Massimo; Poggio, Francesca; Pagani, Olivia; Curigliano, Giuseppe; Mastro, Lucia Del; Paluch-Shimon, Shani; Loibl, Sibylle; Partridge, Ann H; Azim, Hatem A; Peccatori, Fedro A; Demeestere, Isabelle
Abstract: Research question: This study explored the knowledge, attitudes and practice of physicians towards fertility and pregnancy-related issues in young BRCA -mutated breast cancer patients. Design: Physicians attending two international breast cancer conferences completed a 26-item questionnaire exploring fertility preservation, pregnancy during (BCP) or after breast cancer. A statistical comparison was carried out of the responses exploring the same issues in young breast cancer patients overall or specifically in those with BRCA mutations. Results: The survey was completed by 273 physicians. Ovarian tissue cryopreservation (33% versus 40%; P = 0.009) and gonadotrophin-releasing hormone analogues during chemotherapy (74% versus 81%; P = 0.001) were less commonly suggested in BRCA -mutated patients than in the overall breast cancer population. 42% of respondents agreed or were neutral on the statement that ovarian stimulation should not be considered safe in BRCA -mutated breast cancer patients. 45% and 30% agreed or were neutral on the statement that pregnancy in breast cancer survivors may increase the risk of recurrence in BRCA- mutated patients or in the overall breast cancer population, respectively ( P < 0.001). 15% and 3% disagreed that transplanting the cryopreserved ovarian tissue can be considered safe in BRCA- mutated patients or in the overall breast cancer population, respectively ( P < 0.001). 33.3% were against the addition of platinum agents as neoadjuvant chemotherapy in BRCA -mutated patients with BCP. Conclusions: Several misconceptions on fertility preservation and pregnancy-related issues in breast cancer patients persist even among physicians directly involved in breast cancer care. Focused research efforts to address these issues in BRCA -mutated breast cancer patients and education to improve physicians' knowledge and adherence to available guidelines are urgently needed.